(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2008)
In this paper one considers a numerical distance protection based on the dialogue of two protections using the numerical technology of relay 7SA612 and REL316*4, which constitutes a powerful means in term of speed and of selectivity for the elimination of the lines and bars faults in connecting stations, it can also ensure a " distant " help under good conditions. This will make it possible to have permanently two protections of numerical distance to supervise the decentralized production connected through a HV line. Some simulation results are given to confirm that